Theoretical modeling and experimental demonstration of surface plasmon resonance based sensing using phase detection - Ding, Zejun (2010)
This report presents a simplified theoretical modeling and experimental demonstration of surface plasmon resonance based sensing. Two groups of simulation were carried out based on two different configurations using phase shift between p and s polarizations. In order to achieve system optimization, effects of different experimental parameters including gold film thickness, linker layer thickness, sample thickness, incident angle and different gold film permittivity were investigated. Results suggest that the gold thickness should be within 45nm to 50nm to achieve optimize refractive index (RI) resolution of 2.416 x 10-6 unit (RIU), while linker layer and sample thickness greater than 200nm does not affect the sensing. However narrow abrupt phase shift range is a limitation. Experiment was then done based on the optimized theoretical model. Chloride solution was used as sample, obvious phase shift was observed as sample concentration increased. Additional experiment on SPR based imaging was also demonstrated.